Benefits of Systems Integration: Qualitative or Quantitative? - Abu Bakar, Zaitun (Malaysian Journal of Computer Science, 2003)
Systems integration has a slow rate of diffusion and adoption. This is partly due to users and practitioners scepticism on its actual benefits. This paper is based on the findings of a survey conducted in Malaysian public sector IT community. The paper starts with a definition of systems integration and a description on how the study was conducted. This is followed with a depiction on the state of systems integration in the Malaysian public sector, and a discussion on the benefits of systems integration as perceived by the respondents. Finally, a conclusion is drawn on the qualitative and quantitative benefits of systems integration.